Biodigestores e biogás: balanço energético, possibilidades de utilização e mitigação do efeito estufa - Brondani, José Carlos (2010)
Biogas is a gaseous composition formed mainly by the methane gas (CH4) and by the carbon dioxide (CO2), generated especially by microbiologic processes in environment with few or no oxygen. This research was carried out on the biogas produced from the treatment of swine dejections in breathing decomposition and accumulated in the interior of biodigestors, in swine culture in the state of Rio Grande do Sul. Within the range of this present work, the same gas is rusted and it turns into CO2 by the burning in flare. Through the literature review and applied questionnaires, possibilities of treatment of swine objections were raised, through comparative flow chart. Through measuring the biogas flow in appropriate equipments and mathematic analyses, several conclusive results were reached. It was tried to evidence not only the various possibilities of biogas use, mainly the generation of electric energy, but also the heating of swine culture in the winter. It was approached the necessary equipments to invest in the first item mentioned, as well as deadlines for these investments return. From another point of view , it was evidenced the biogas nonuse in aid of the swine culture, but the investment in a Mechanism of Clean Development (MCD) to obtain the Credits of Carbon, where it was observed the great difficulties, mainly financial, to a swine breeder implant the same. Several technical and economical possibilities to mitigate the greenhouse effect were analyzed.